Histioea magistrae sp. nov. (Lepidoptera: Erebidae: Arctiini) from southeastern Amazonia, Peru - Grados, Juan (2015)
Adult males of a new species of Euchromiina (Arctiini), Histioea magistrae, from southeastern Amazonia, Peru, are described, illustrated and compared to the similar species Histioea hoffmannsi Rothschild, 1911.